Origin of superior hardening properties in KCuTa3O9-doped K0.5Na0.5NbO3 lead-free piezoelectric ceramics. Issue 17 (1st December 2017) - Wang, Tao; He, Lihua; Deng, Yunlong; Zheng, Qiaoji; Li, Qiang; Jiang, Na; Xu, Chenggang; Cao, Xingzhong; Lin, Dunmin
Abstract: K0.5 Na0.5 NbO3 + x mol KCuTa3 O9 lead-free piezoelectric ceramics with superior hardening properties were synthesized by a solid-state reaction method. The addition of a small amount of KCuTa3 O9 ( x ≤ 0.04) induces the formation of ( C u N b ′ ′ ′ − V O ) ′ (DC1) and ( V O − C u N b ′ ′ ′ − V O ) (DC2) defect dipoles; however, DC2 becomes dominant in the ceramics with high levels of KCuTa3 O9. The DC1 can provide a restoring force to reverse the switched polarization, inducing double hysteresis loops, while DC2 slightly impedes polarization back-switching. Because of the combination of DC1 and DC2 associates, the ceramics become gradually "hardened" with x increasing from 0 to 0.01, giving a superhigh mechanical quality factor Q m of 2494 at x = 0.01, and then are gradually softened with x further increasing to 0.07, exhibiting a relatively low Q m of 549 at x = 0.07. Our study shows that the control of defect structures can effectively tailor the ferroelectricity and piezoelectricity of K0.5 Na0.5 NbO3 -based lead-free ceramics.